The impact of perineal massage during pregnancy on perineal laceration during childbirth and postpartum: A randomized clinical trial study - Roonak Shahoei; Lila Hashemi-Nasab; Golbahar Gaderkhani; Farzaneh Zaheri; Faranak Shahoei (Chronic Diseases Journal, 2016)
BACKGROUND: This study was aimed to investigate the effect of perineal massage during pregnancy on perineal pain and lacerations.